Semi-quantitative model of the gating of KcsA ion channel. 1. Geometry and energetics of the gating - Kharkyanen, V.N.; Yesylevskyy, S.O.; Berezetskaya, N.M.; Boiteux, C.; Ramseyer, Ch. (Вiopolymers and Cell, 2009)
The aim of this series of papers is to develop the semi-quantitative theory of the gating of KcsA channel. For this purpose the available structural and electrophysiological data and the results of molecular dynamics simulations were used in the context of the concept of dynamical self-organization. In the first paper we describe the simplified model of the geometry and energetics of the gating process. This work is the first successful attempt of combining the structure and dynamics of a real protein and the general concept of dynamic self-organization. Мета даної серії робіт полягає у розробці напівкількісної теорії воротних процесів в іонному каналі KcsA. Для цього залучено доступні експериментальні дані, а також результати молекулярної динаміки у контексті концепції динамічної самоорганізації. У першій роботі серії представлено спрощену модель геометрії та енергетики воротних процесів. Наведено першу успішну спробу об’єднання даних щодо структури та динаміки реального білка з концепцією динамічної самоорганізації. Целью данной серии работ является разработка полуколи- чественной теории воротных процессов в ионном канале KcsA. Для этого использованы доступные экспериментальные данные, а также результаты молекулярной динамики в контексте концепции динамической самоорганизации. В первой работе серии представлена упрощенная модель геометрии и энергетики воротных процессов. Приведена первая успешная попытка объединения данных о структуре и динамике реального белка с концепцией динамической самоорганизации.